Qingfei Formula Protects against Human Respiratory Syn cytial Virus-induced Lung Inflammatory Injury by Regulating the M APK Signaling Pathway - Sun, Ya-Lei; Zhao, Pei-Pei; Zhu, Cheng-Bi; Li, Xin-Min; Yuan, Bin (Combinatorial Chemistry & High Throughput Screening, 2024)
Objective: Qingfei formula (QF) is an empirical formula that shows good clinical efficacy in treating human respiratory syncytial virus pneumonia (RSVP). However, the underlying mechanism remains unclear. This study explores the possible pharmacological actions of QF in RSVP treatment. Methods: We used a network pharmacology approach to identify the active ingredients of QF, forecast possible therapeutic targets, and analyze biological processes and pathways. Molecular docking simulation was used to evaluate the binding capability of active ingredients and therapeutic targets. Finally, in vivo experiments confirmed the reliability of network pharmacology-based prediction of underlying mechanisms. Results: The study identified 92 potential therapeutic targets and corresponding 131 active ingredients. Enrichment analysis showed that QF downregulated the MAPK signaling pathway and suppressed the inflammatory injury to the lungs induced by the RSV virus. Molecular docking simulations demonstrated that the core active ingredients of QF could stably bind to genes associated with the MAPK signaling pathway. QF had a protective effect against pneumonia in RSV-infected mice. The QF group exhibited a significant reduction in the levels of inflammatory mediators, interleukin- 6 (IL-6), interleukin-8 (CXCL8, IL-8), and P-STAT3, compared to the RSV-induced group. The QF group showed remarkably inhibited MAPK1+3(P-ERK1+2) and MAPK8(P-JNK) protein expression. Conclusion: The current study showed that QF downregulated the MAPK signaling pathway, which inhibited pulmonary inflammation triggered by RSV infection. This study recommends the appropriate use of QF in the clinical management of RSVP.
Keywords: network pharmacology